Metabolic patterns and seizure outcomes following anterior temporal lobectomy. Issue 2 (17th January 2019) - Cahill, Varduhi; Sinclair, Benjamin; Malpas, Charles B.; McIntosh, Anne M.; Chen, Zhibin; Vivash, Lucy E.; O'Shea, Marie F.; Wilson, Sarah J.; Desmond, Patricia M.; Berlangieri, Salvatore U.; Hicks, Rodney J.; Rowe, Christopher C.; et al.
Abstract : Objective: We investigated the relationship between the interictal metabolic patterns, the extent of resection of 18 F‐fluorodeoxyglucose positron emission tomography ( 18 FDG‐PET) hypometabolism, and seizure outcomes in patients with unilateral drug‐resistant mesial temporal lobe epilepsy (MTLE) following anterior temporal lobe (TL) resection. Methods: Eighty‐two patients with hippocampal sclerosis or normal magnetic resonance imaging (MRI) findings, concordant 18 FDG‐PET hypometabolism, and at least 2 years of postoperative follow‐up were included in this 2‐center study. The hypometabolic regions in each patient were identified with reference to 20 healthy controls ( p < 0.005). The resected TL volume and the volume of resected TL PET hypometabolism (TLH) were calculated from the pre‐ and postoperative MRI scans coregistered with interictal 18 FDG‐PET. Results: Striking differences in metabolic patterns were observed depending on the lateralization of the epileptogenic TL. The extent of the ipsilateral TLH was significantly greater in left MTLE patients (p < 0.001), whereas right MTLE patients had significantly higher rates of contralateral (CTL) TLH ( p = 0.016). In right MTLE patients, CTL hypometabolism was the strongest predictor of an unfavorable seizure outcome, associated with a 5‐fold increase in the likelihood of seizure recurrence (odds ratio [OR] = 4.90, 95% confidence interval [CI] = 1.07–22.39, p = 0.04). In left MTLE patients, greater extent of resection of ipsilateral TLH was associated with lower rates of seizure recurrence ( p = 0.004) in univariate analysis; however, its predictive value did not reach statistical significance (OR = 0.96, 95% CI = 0.90–1.02, p = 0.19). Interpretation: The difference in metabolic patterns depending on the lateralization of MTLE may represent distinct epileptic networks in patients with right versus left MTLE, and can guide preoperative counseling and surgical planning. Ann Neurol 2019; 1–10ANN NEUROL 2019;85:241–250.